1988
DOI: 10.1161/01.hyp.11.5.397
|View full text |Cite
|
Sign up to set email alerts
|

Peptide hormones and the regulation of sodium excretion.

Abstract: KEY WORDS • peptide hormones • hormone receptors • intracellular messengers glomerular filtration rate • sodium reabsorption • sodium excretion T WENTY years ago, intensive research led to the delineation of the role played by alterations in blood composition in mediating the natriuresis that resulted from the infusion of colloidfree isotonic saline solutions into humans and experimental animals. Results of this research indicated that changes in renal hemodynamics (glomerular filtration rate [GFR], renal bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…While endogenous opioids mediate antinatriuretic responses under these conditions, it appears that, under certain conditions, opioid systems may interact with mechanisms that enhance the renal excretion of sodium. For instance, Humphreys and Lin (1988) have shown that y-melanocyte stimulating hormone, a peptide derived from the 0-endorphin precursor molecule pro-opiomelanocortin, is released from the pituitary during acute unilateral nephrectomy and produces a natriuresis in the remaining contralateral kidney. A role for central endogenous opioids in this renal response was suggested because centrally administered naloxone blocks the reflex natriuresis after acute unilateral nephrectomy (Lin & Humphreys 1985).…”
Section: Endogenous Opioid Control Of Renal Functionmentioning
confidence: 99%
“…While endogenous opioids mediate antinatriuretic responses under these conditions, it appears that, under certain conditions, opioid systems may interact with mechanisms that enhance the renal excretion of sodium. For instance, Humphreys and Lin (1988) have shown that y-melanocyte stimulating hormone, a peptide derived from the 0-endorphin precursor molecule pro-opiomelanocortin, is released from the pituitary during acute unilateral nephrectomy and produces a natriuresis in the remaining contralateral kidney. A role for central endogenous opioids in this renal response was suggested because centrally administered naloxone blocks the reflex natriuresis after acute unilateral nephrectomy (Lin & Humphreys 1985).…”
Section: Endogenous Opioid Control Of Renal Functionmentioning
confidence: 99%
“…They exist in a, b and g primary structures, which share a core heptapeptide sequence of amino acids [1][2][3]. Although highly conserved among mammalian species, the functions of these peptides remained elusive until the identification in recent years of a family of five melanocortin receptors (MC1-R-MC5-R), which mediate their cellular actions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms, neural [l], circulatory [2] and humoral [3], have been proposed to explain the natriuresis occurring after intravenous (i.v.) infusion of sodium (Na+) chloride.…”
Section: Introductionmentioning
confidence: 99%